ANALISIS LAYANAN PINJAMAN BERBASIS FINTECH PADA FITUR SHOPEE PINJAM (SPINJAM) BERDASARKAN KOMPILASI HUKUM EKONOMI SYARIAH - Fatimah, Sitti (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2021)
This study aims to describe the mechanism and practice of fintech-based loan services on the SPinjam feature which is analyzed based on the Sharia Economic Law Compilation. This type of research is an empirical legal research using a case approach through observation, interviews and documentation instruments. The data analysis technique is descriptive using the Miles and Huberman model through three activity lines, namely data reduction, data display, and conclusion drawing/verification. The results of this study indicate that: (1) There are two steps to getting fintech-based loan services on the SPinjam feature, namely activating the SPinjam feature and following the loan application procedure on the SPinjam feature. In practice, the SPinjam feature has set the smallest interest rate of 2.45%, administrative fees of up to 3%, and additional funding sanctions of Â± 5.0% of the remaining loan principal for late installment payments. Payments can be made through Indomaret outlets, Alfamart, Bank Transfers, and others. (2) Judging from the compilation of sharia economic law, the practice of fintech-based lending services on the SPinjam feature is not justified just because users both agree, because in its operation it applies an interest system that is prohibited in Islam.